HOXD3 Up-regulating KDM5C Promotes Malignant Progression of Diffuse Large B-Cell Lymphoma by Decreasing p53 Expression - YuYing Cui; Chao LV; Yu Wen; Dongmei Zhao; Yu Yang; Hongbin Qiu; Chennan Wang (Balkan Medical Journal, 2022)
Background: Diffuse large B-cell lymphoma is a type of B-cell non-Hodgkin lymphoma with a high incidence. About one-third of patients are resistant or eventually relapse. The prognosis for patients with relapsed/resistant diffuse large B-cell lymphoma who need salvage therapy is not optimistic. Aims: To explore whether homebox D3 binding to lysine (K)-specific demethylase 5C promoted malignant progression of diffuse large B-cell lymphoma by decreasing p53 expression. Study Design: Cell culture study. Methods: The mRNA and protein expression of lysine (K)-specific demethylase 5C and homebox D3 in cells were respectively detected by real-time quantitative polymerase chain reaction analysis and Western blot. Real-time quantitative polymerase chain reaction analysis and Western blot were also applied to determine the transfection effects of shRNA-KDM5C or OeHOXD3 in OCI-Ly7 cells. After transfection, the cell viability, proliferation, and apoptosis were respectively analyzed by Cell Counting Kit-8 assay, EdU staining, and acridine orange—ethidium bromide staining. The interaction between homebox D3 and lysine (K)-specific demethylase 5C promoter was verified by the dual-luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay. Results: Lysine (K)-specific demethylase 5C mRNA expression (HBL1 2.84 ± 0.29; SUDHL4 3.53 ± 0.21; OCI-Ly8 4.06 ± 0.24; OCI-Ly7 5.03 ± 0.28 vs. GM12878 1.00 ± 0.07; all P < .001) and protein expression (HBL1 1.52 ± 0.06; SUDHL4 1.77 ± 0.10; OCI-Ly8 2.34 ± 0.07; OCI-Ly7 2.78 ± 0.07 vs. GM12878 1.00 ± 0.07; all P < .001) in DLBCL cells were higher than that in GM12878 cells and showed the highest in OCI-Ly7 cells. Homebox D3 mRNA (OCI-Ly7 3.85 ± 0.17 vs. GM12878 1.00 ± 0.05; P < .001) and protein (OCI-Ly7 1.73 ± 0.10 vs. GM12878 1.00 ± 0.06; P < .001) expression were also highly expressed in OCI-Ly7 cells. Moreover, down-regulation of lysine (K)-specific demethylase 5C suppressed the viability and proliferation and enhanced the apoptosis of OCI-Ly7 cells. Knockdown of lysine (K)-specific demethylase 5C decreased the B-cell lymphoma 2 expression while increased the expression of Bax, cleaved caspase 3, cytochrome C, p53, and p21. The transcription factor homebox D3 was confirmed to interact with the lysine (K)-specific demethylase 5C promoter. Homebox D3 overexpression could reverse the regulating effect of down-regulation of lysine (K)-specific demethylase 5C on the OCI-Ly7 cells. Conclusion: Homebox D3 up-regulating lysine (K)-specific demethylase 5C promotes malignant progression of diffuse large B-cell lymphoma by decreasing p53 expression.